2019
DOI: 10.32615/bp.2019.003
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth elements in plants

Abstract: Since 1960, the positive effects of rare earth elements (REE) on crop physiology have been observed, and support for photosynthesis, biomass accumulation, secondary metabolites, or enzymes has been reported in 40% of studies. A higher content of chlorophylls a and b as well as carotenoids have been found along with an increased efficiency of photosystem II photochemistry and electron transfer rates. An increased activity of a key photosynthetic enzyme was also found in several plants growing in soil with a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 102 publications
1
48
0
2
Order By: Relevance
“…Major reviews concerning adverse effects on soil organisms include those of Hu, Shen, and Zhao (2006), Redling (2006), El-Ramady (2010), Rim (2016), Kovaříková, Tomášková, and Soudek (2019), and Agathokleous, Kitao, and Calabrese (2019). Examples of adverse effects for major classes of organisms are given in Appendix 3.…”
Section: Examples Of Lanthanide Effects On Organisms Exposed In Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Major reviews concerning adverse effects on soil organisms include those of Hu, Shen, and Zhao (2006), Redling (2006), El-Ramady (2010), Rim (2016), Kovaříková, Tomášková, and Soudek (2019), and Agathokleous, Kitao, and Calabrese (2019). Examples of adverse effects for major classes of organisms are given in Appendix 3.…”
Section: Examples Of Lanthanide Effects On Organisms Exposed In Soilsmentioning
confidence: 99%
“…Thus, aberrations might above all be found for Ce (Wyttenbach, Furrer, Schleppi, & Tobler, 1998). Factors influencing the Ce and Eu anomalies have been discussed by Kovaříková, Tomášková, and Soudek (2019).…”
Section: A231 Aberrations For Ce Eu and Ybmentioning
confidence: 99%
“…However, higher doses of La may unbalance cell homeostasis by causing damage in the external membrane of the chloroplast, decreasing the concentrations of mineral nutrients in this organelle, especially those of P, Mg, K, Ca, Mn, Fe, Ni, Cu, Zn, and Mo, and disrupting Chl biosynthesis, which lead to a drastic reduction in photosynthesis, and cause lower growth or even negative impacts on plant performance (Hu et al 2016b). Additionally, REEs promoted the biosynthesis of the secondary metabolites, such as flavonoids, isoflavones, sesquiterpenoids, and benzyl ethanol glycosides in medicinal plant cells (Yuan et al 2002, Ouyang et al 2003, Huang 2006, Zhou et al 2010, Zhou et al 2012, Kovaříková et al 2019. Yuan et al (1993) found that 20 mg[La(NO3)3] kg -1 promoted the accumulation of alkaloids of Catharanthus roseus in cell cultures.…”
Section: La Increases Corm Yield and Kgmmentioning
confidence: 99%
“…Beneficial effects in plants have occasionally been reported for different elements with either a single +3-oxidation state, such as Al and lanthanum (La), or with multiple valences, including +3, like Cr, Ti, V, and certain rare earth elements [15,16,17,18]. However, there is no evidence for the direct metabolic functions of these elements.…”
Section: Trivalent (+3) Elements: Essentiality Beneficial Effectsmentioning
confidence: 99%